Aplikasi Almihjam sebagai Media Edukasi Titik Bekam untuk Peningkatan Literasi Kesehatan Masyarakat Bima - Fitriati, Ita; Cahyadi, Anggih Tri; Suryani, Lili; Ghazali, Muhammad (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2025)
Low health literacy impacts individuals' ability to make decisions, access services, and understand medical information. Improving health literacy is a critical priority for improving the quality of life for communities, including in Bima Regency-NTB. However, health literacy studies are still limited, both in the development of measurement tools and educational media, necessitating innovations tailored to local needs. This research responds to this situation by developing the Almihjam application, a digital educational media for cupping therapy, as cupping is a popular traditional treatment in Bima. The research objective is to produce a valid, effective, and publicly accepted cupping education application, thereby improving health literacy and encouraging safe cupping practices in accordance with local medical and cultural principles. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation). Expert validation results showed a feasibility score of 78.5%, indicating the application is feasible. Health literacy data shows that the community has positive knowledge and attitudes toward cupping, although its practice is still limited. User response has been very high, with average ratings of satisfaction, content clarity, and feature usefulness above 95%. Thus, the Almihjam app has the potential to be an effective digital innovation for improving health literacy among the Bima community.